Optimizing the Performance of Narcotics Detectives in Handling Narcotics Offenders through Restorative Justice in the Legal Area of Polresta Surakarta - Rafly Akbar (Tanggon Kosala, 2023)
The high number of narcotics crimes in the legal area of Polresta Surakarta is partly caused by the low performance of narcotics detectives who have not made efforts for rehabilitation and have not applied restorative justice approaches to narcotics offenders in the legal area of Polresta Surakarta. This background motivates the author to write a final project related to the optimization of the performance of narcotics detectives in handling narcotics offenders through restorative justice. The purpose of this writing is to describe the mechanism of the investigation of narcotics crimes by narcotics detectives in Polresta Surakarta and to describe the organizational resources of Satresnarkoba Polresta Surakarta in handling narcotics offenders. The author uses a qualitative approach with data collection techniques through interviews, observations, and document studies. The author uses organizational resource management theory, SWOT analysis theory, law enforcement theory, investigation concepts according to Perkap No.6 of 2019, concepts of narcotics distributors and offenders, restorative justice concepts and theories as analytical tools to explain the problems and limitations of the writing. The results of this final project show that the performance of narcotics detectives in handling narcotics offenders through restorative justice in Polresta Surakarta is not yet optimal due to the lack of a rehabilitation justice system (RJS) and the lack of application of restorative justice that is in accordance with Perpol No. 8 of 2021. There is also poor coordination between narcotics detectives in Polresta Surakarta with BNNK Surakarta and Kejari Kota Surakarta. In addition, the legal process for narcotics offenders in Polresta Surakarta involves detention, and the organizational resources of Satresnarkoba Polresta Surakarta do not support the detectives in handling narcotics offenders. Therefore, problemsolving steps are expected to optimize the performance of narcotics detectives in handling narcotics offenders in Polresta Surakarta.